The first look at narrow-line Seyfert 1 galaxies with eROSITA - Grünwald, G.; Boller, T.; Rakshit, S.; Buchner, J.; Dauser, Thomas; Freyberg, M.; Liu, T.; Salvato, M.; Schichtel, A. (Astronomy & Astrophysics, 2023)
We present the first look at the spectral and timing analysis of narrow-line Seyfert 1 galaxies (NLS1s) with the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum-Roentgen-Gamma (SRG) mission. The sample of approximately 1200 NLS1s was obtained via a cross-match between the first eROSITA All-Sky Survey (eRASS1) catalogue and the catalogue of spectroscopically selected NLS1s from the twelfth data release of the Sloan Digital Sky Survey (SDSS) DR12. The X-ray spectral analysis is based on a simple power-law fit. The photon index distribution has a mean value of about 2.81-±-0.03, as expected from previous X-ray studies of NLS1s. Interestingly, it is positively skewed, and about 10% of the sources are located in the super-soft tail of photon indices larger than 4. These sources are of further interest as their source counts run into the X-ray background at values at around 1 keV. We argue that ionised outflows have been detected by eROSITA and may account for some of the extreme spectral steepness, which is supported by correlations found between the photon index and optical outflow parameters. We analysed the intrinsic X-ray variability of the eRASS1 to eRASS3 light curves of the sample but do not find significant variability either during the individual survey scans or between them.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Accretion; Accretion discs; Galaxies: Seyfert; Surveys; X-rays: general